Levels of Advanced Oxidation Protein Products in Blood Plasma of Peri- and Postmenopausal Women with Insomnia - N. V. Semenova; I. M. Madaeva; A. S. Brichagina; L. I. Kolesnikova (Acta Biomedica Scientifica, 2021)
Background. Insomnia occurs in more than half of menopausal women. These disorders can contribute to a change in the prooxidant-antioxidant balance, causing the damage to structural cellular elements. Currently, there is a lack of research on this issue.Aim. To carry out a comparative analysis of the level of advanced oxidation protein products in in periand postmenopausal women with insomnia.Materials and methods. The study included peri(n = 30) and postmenopausal (n = 60) women, who were divided into 2 groups (control and main groups) in each menopausal phase after being questioned using special sleep questionnaires: Insomnia Severity Index; Epworth Sleepiness Scale; Munich Chronotype Questionnaire. The advanced oxidation protein products (AOPP) levels was determined by immunoenzymatic assay using ImmunDiagnostik (German) kits on a BioTek EL×808 (USA) analyzer. Statistical analysis was performed using Mann – Whitney test.Results. Comparative analysis of the AOPP levels in control groups, depending on the menopausal periods, showed an increase in their levels in the postmenopausal period as compared to perimenopause (p < 0.05). When comparing the AOPP levels between the control and the main group in different menopausal periods, statistically significant differences were revealed only in the perimenopausal period towards a higher content in women with insomnia (p < 0.05). The presence of insomnia in postmenopausal women is accompanied by a higher AOPP levels as compared to the perimenopausal women (p < 0.05).Conclusion. The obtained results indicate the association between insomnia and oxidative proteins modification only in the perimenopausal period.